Phytosanitary assessment of the state of populations of the Japanese grape leafhopper (Arboridia kakogawana Mats.) in grape agrocenoses of the Northern Black Sea region of Ukraine - Baranets, L.; Balan, H.; Perepelytsya, O.; Leshchenko, A. (Quarantine and plant protection, 2022)
Goal. To clarify the species composition of the order Cicada (Hemiptera: Cicadinea (Auchenorrhyncha)) and their distribution in the grape agrocenoses of the Northern Black Sea Coast of Ukraine. Investigate the peculiarities of the seasonal dynamics of the Japanese grape cicada (Arboridia kakogawana Mats.) and identify the varieties that are most susceptible to damage by this leafhopper. Methods. Phytosanitary monitoring of leafhopper distribution in grape agrocenoses, the results of which determined the species composition of cicadas, the number of populations and the nature of plant population. The study of seasonal dynamics and determination of the flight peaks of the imago of the Japanese grape leafhopper was carried out with the help of yellow glue traps. Results. The data of the increase of species composition and expansion of the range of the order Cicadinea in agrocenoses of vineyards in the conditions of the Northern Black Sea zone of Ukraine are presented. The most significant changes were noted in invasive species of leafhoppers. The reasons are the process of adapting the development of cicadas to the conditions of grape ecosystems in the region. The dynamics of the number of Japanese grape leafhopper (Arboridia kakogawana Mats.) is given and the periods of its maximum abundance in industrial vineyards are traced. The number of generations of A. kakogawana was determined and the varieties that are most susceptible to damage by this cicada are indicated. Conclusions. According to the results of the research, 12 species of leafhoppers from different ecological and trophic groups belonging to 5 families were identified. It was noted that among the studied leafhoppers, the most common is the invasive species of the Japanese grape leafhopper, which ranges from 28.7 to 46.5% of the total number of populated bushes. It is noted that in the conditions of the Northern Black Sea leafhopper develops in three generations. Adults are caught from early June to mid-October. During this time, 3 peaks of leafhopper are recorded — the first — in mid-July, the second — in the first decade of August and the third peak — in early September. The development cycle of one generation is about 35—40 days. Migration to wintering grounds begins in mid-September. It was found that all surveyed grape varieties were inhabited by Japanese grape leafhopper, but it was analyzed that the number of populations in the varieties is different. Varieties with medium or more intense leaf pubescence were more intensively populated, such as Cabernet Sauvignon, Sukholimansky White, Odesa Souvenir, Chardonnay, Odessa Black, Rkatsiteli and Muscat Tairovsky. The smallest number of leafhoppers was found on varieties without pubescence or with weak pubescence of leaves on the underside, it is Arcadia, Flora, Riddle, Raisin Tairovsky, Kardishah and others.